Devolving English literature - Crawford, Robert, 1959- (Edinburgh University Press, 2000)
"This book looks at the rise and fall of 'Britishness' in literature over the last three centuries. Arguing that for much of its history the subject of 'English Literature' has been bound up with an assumed English cultural centre, Devolving English Literature examines the literary construction and questioning of a British (rather than simply English) literary identity. Surveying eighteenth- and nineteenth-century writers, including Robert Burns, James Boswell, Walter Scott and Thomas Carlyle, Robert Crawford remaps literary history. He argues that Scottish and non-metropolitan authors left a crucial legacy to American literature, to the developing subject of anthropology, and to twentieth-century Modernism. In the work of T.S. Eliot, Ezra Pound, James Joyce, Hugh MacDiarmid and other Modernists there persist vitally 'provincial' as well as national elements. These continue to nourish the verse of sophisticated post-British 'barbarian' poets such as Seamus Heaney, Tony Harrison, Douglas Dunn, Les Murray and Derek Walcott. More than that, they are bound up with the contemporary literature and politics of Britain after devolution."--Jacket